Transforming Educational Paradigms: How Micro Learning Shapes Student Understanding, Retention, and Motivation? - Astiwardhani, Winny; A. Sobandi (Journal of Education Action Reseach, 2024)
Microlearning is an increasingly relevant approach to learning in the digital age, prioritizing information in small chunks such as short videos, infographics, or interactive quizzes to improve student understanding, knowledge retention, engagement, and motivation. Previous research shows the effectiveness of microlearning in various contexts, such as higher education, corporate training, and professional development. However, there are challenges in defining and measuring its effectiveness and its impact on student learning outcomes. This study aims to analyze a systematic literature review (SLR) to understand the efficacy of microlearning and its influencing factors more holistically. This study is a qualitative research using the SLR method. This study used a data collection method in the form of systematic observation. This study involved 23 eligible articles. After the data was collected, it was analyzed using the qualitative descriptive data analysis technique. As a result of the various references provided, the overview of the literature found on microlearning covers a wide range of relevant topics and applications. Thus, it can be concluded that microlearning has demonstrated its effectiveness in improving students' understanding of concepts and ability to retain knowledge in several areas of education. Thus, this research will provide deeper insights into the potential and effective micro-learning strategies in various educational contexts.